2021
DOI: 10.1002/cbdv.202100466
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents from Aerial Parts of Baccharis sphenophylla and Effects against Intracellular Forms of Trypanosoma cruzi

Abstract: The hexane extract from aerial parts Baccharis sphenophylla Dusén ex Malme (Asteraceae) displayed activity against amastigote forms of Trypanossoma cruzi and was subjected to chromatographic steps to afford one unreported – 7α‐hydroxy‐ent‐abieta‐8(14),13(15)‐dien‐16,12β‐olide (1) and three known diterpenes – ent‐kaur‐16‐en‐19‐oic acid, (2), grandifloric acid (3), and 15β‐tiglinoyloxy‐ent‐kaur‐16‐en‐19‐oic acid (4), two sesquiterpenes – spathulenol (5) and oplopanone (6) – as well as hexacosyl p‐coumarate (7). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…The chromatographic fractionation of the DCM fraction allowed the isolation of compounds 1–3 ( Figure 2 ). Compound 1 exhibited both 1 H and 13 C NMR data compatible with the ent -kaurenoic acid, a diterpenoid previously isolated from B. sphenophylla [ 26 ]. Compounds 2 and 3 showed singlets at δ 6.80 and δ 6.66 in their 1 H NMR spectra, respectively, which were assigned to H-3 from a flavone skeleton.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…The chromatographic fractionation of the DCM fraction allowed the isolation of compounds 1–3 ( Figure 2 ). Compound 1 exhibited both 1 H and 13 C NMR data compatible with the ent -kaurenoic acid, a diterpenoid previously isolated from B. sphenophylla [ 26 ]. Compounds 2 and 3 showed singlets at δ 6.80 and δ 6.66 in their 1 H NMR spectra, respectively, which were assigned to H-3 from a flavone skeleton.…”
Section: Resultsmentioning
confidence: 65%
“…In our continuing efforts to search for bioactive compounds in Baccharis species [ 24 , 25 ], we have focused on B. sphenophylla Dusén ex Malme ( Figure 1 ), a rare and endemic plant found in the highlands of south and southeast Brazil; specifically, in the states of Paraná, São Paulo, and Minas Gerais. Previously, the n -hexane extract of this species was studied, demonstrating a long-chain ester of p -coumaric acid, two sesquiterpenoids, and four diterpenoids with antitrypanosomal effects [ 26 ]. Herein, we describe the isolation, structure, and antiradical activities of compounds obtained from polar extracts of the leaves of B. sphenophylla .…”
Section: Introductionmentioning
confidence: 99%
“…BALB/c mice were utilized for T. cruzi maintenance infection and peritoneal macrophage collection. 33 The mice were obtained from the animal breeding facility at the Instituto Adolfo Lutz -São Paulo, Brazil and maintained in sterilized boxes with absorbent material under a controlled environment. Food and water were given ad libitum.…”
Section: Bioassay Proceduresmentioning
confidence: 99%
“…Four diterpenoids (Figure 1 previously reported in the literature. [10,11] 2.2 | Absorption, distribution, metabolism, and excretion (ADME) properties evaluation of compounds 1-4…”
Section: Chemical Characterization Of Compounds 1-4mentioning
confidence: 99%
“…Ent-kaurenoic acid (1) has been reported in the literature as the main metabolite isolated from different plants belonging to Baccharis species and its biological potential includes antiviral, [20] anthelminthic, [21] and antiparasitic [10,11] activities. Additionally, it has been reported that ent-kaurenoic acid (1) displayed activity against human leukemia [22] and gastric cancer [23] cell lines, as well as induced apoptosis in HeLa cells.…”
Section: Cytotoxicity Effects Of Compounds 1-4mentioning
confidence: 99%